Frozen Section Library: Pancreas - Frankel, Wendy L.; Proca, Daniela M.; SpringerLink (Online service) (Boston, MA : Springer US, 2011)
Frozen Sections are performed while a patient is undergoing surgery as a basis for making an immediate diagnosis that will impact treatment decisions. Frozen section diagnosis is often a highly demanding situation for the pathologist who must render a diagnosis quickly for the patient and surgeon. The Frozen Section Library series will provide concise, user-friendly, site specific handbooks that are well illustrated and highlight the pitfalls, artifacts and differential diagnosis issues that arise in the hurried frozen section scenario.
Introduction -- Clinical Indications and Surgeons$1 (BExpectations -- The Distinction between Chronic Pancreatitis and Adenocarcinoma -- Variants of Pancreatic Adenocarcinoma and Pancreatic Intraepithelial Neoplasia -- Cystic Lesions in the Pancreas -- Other Pancreatic Tumors -- Secondary Tumors and Miscellaneous Lesions Involving the Pancreas -- Metastases, Resectability and Margins -- Suggested Reading.s
Keywords: Medicine; Pathology; Medicine & Public Health; Pathology